Bridging the Digital Divide: Understanding the Awareness-Capability Paradox in Rural Enterprise Digital Transformation - Abdurokhim Abdurokhim (Winter Journal: IMWI Student Research Journal, 2026)
Digital transformation promises rural economic development through expanded market access and enhanced efficiency, yet adoption rates remain disappointingly low despite widespread awareness. Why does awareness of digital importance fail to translate into capability in rural enterprises? Through qualitative investigation of 10 village-owned enterprises (BUMDES) in Indonesia using semi-structured interviews (n=20) and focus group discussions (n=24), we identify five interconnected barriers preventing awareness-to-action conversion: (1) resource scarcity trap - digital investments compete with survival needs, (2) knowledge-action gap - managers lack operational know-how despite recognizing importance, (3) ecosystem deficits - inadequate infrastructure and support constrain capability building, (4) capability-confidence mismatch - low self-efficacy inhibits experimentation, and (5) institutional inertia - routines and norms resist change. These mechanisms create self-reinforcing cycles sustaining persistent awareness-capability gaps despite strong digital aspirations. Findings challenge linear technology adoption assumptions, extend Resource-Based View and organizational learning theory to resource-constrained contexts, and inform intervention design emphasizing integrated support packages addressing multiple barriers simultaneously rather than isolated awareness campaigns or standalone training programs.